2014
DOI: 10.1177/0954409714561708
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of the mechanical behaviour of insulated rail joints due to impact loadings

Abstract: Insulated rail joints (IRJs) are safety-critical components in the signalling system of rail corridors. They are subjected to dynamic loads generated by heavy rolling-stock/track- system interactions and degrade faster than the other components of the rail track. Degraded IRJs diminish the reliability of the signalling system, thus posing a serious threat to the safety of rail operations. Therefore, there is a pressing need to closely examine the failure mechanisms of the end posts made of insulated material a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Sandstrom and Ekberg [8] employed a 3D elastoplastic FEM model to predict the plastic deformation and fatigue resulting from wheel-IRJ impacts by capturing the accumulation of plastic strain. Mandal and Dhanasekar [9] proposed a sub-modeling FE strategy to examine the ratcheting failure of IRJs, and the same strategy was adopted by Mandal [10] to study the influences of end-post materials on railhead deterioration at IRJs. Zong et al [11] applied an implicit-explicit FE model to simulate rail/wheel dynamic contact impact and railhead damage in the vicinity of IRJ.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sandstrom and Ekberg [8] employed a 3D elastoplastic FEM model to predict the plastic deformation and fatigue resulting from wheel-IRJ impacts by capturing the accumulation of plastic strain. Mandal and Dhanasekar [9] proposed a sub-modeling FE strategy to examine the ratcheting failure of IRJs, and the same strategy was adopted by Mandal [10] to study the influences of end-post materials on railhead deterioration at IRJs. Zong et al [11] applied an implicit-explicit FE model to simulate rail/wheel dynamic contact impact and railhead damage in the vicinity of IRJ.…”
Section: Introductionmentioning
confidence: 99%
“…Although many researchers believe that dynamic effects play certain roles during wheel-rail impacts [4,6-8, 10,15,16] , quasi-static wheelrail contact is still generally assumed in the FE models [2,4,[8][9][10] . Transient solutions that can reflect dynamic effects in the wheel-rail impact contact have rarely been studied, which may be because well-accepted methods [3,5,[17][18][19] capable of resolving common wheel-rail contact problems are generally based on the quasi-static contact assumption, and the dynamic effects during contact are therefore not necessarily considered in many situations.…”
Section: Introductionmentioning
confidence: 99%
“…This type of element was considered because it is widely used in elastic-plastic material deformation. 24,25 Finally, in the job module, the simulation was completed to obtain the displacement DOFs at the nodes of the global model and the displacement DOFs were then used to run a separate sub-model of rail ( Figure 6) which is discussed in the following section. The positive global coordinate directions are shown in Figure 6 such that the '3' direction is for longitudinal, '2' is for vertical and '1' is for lateral.…”
Section: Global Modelling Strategymentioning
confidence: 99%
“…57 These approaches have been verified and/or validated to be effective and efficient enough for addressing the problems of wheel–rail (W/R) contact in elasticity as well as in the cases of quasi-static and/or low-frequency dynamics. 2,812 Regarding the complex problems with both realistic contact geometries and material plasticity considered, finite element (FE) method, as opposed to the aforementioned approaches, appears to be much preferable and powerful for ensuring the desired solutions.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the contact pressure and the micro-slip were critical variables responsible for the surface damage of crossing rail. More recent modeling advances of W/R interaction, including the development of implicit FE models 11,12,23 (i.e. not referenced but of equal importance as those explicit FE models), can be found in Meymand et al.…”
Section: Introductionmentioning
confidence: 99%